The relevance of adhesion molecules in the classification of squamous cell carcinoma of the head and neck. - Lieder, A; Prior, T; Wood, K; Werner, J (2005)
BACKGROUND: Clinical studies have demonstrated increased serum levels of E-selectin, P-selectin and VCAM-1 in patients with squamous cell carcinomas, which correlate with expression in the primary tumour. For this reason, selectin expression may also support the diagnosis and be of prognostic value in squamous cell carcinoma of the head and neck (SCCHN). MATERIALS AND METHODS: Using immunohistochemistry, the expressions of E- and P-selectin and VCAM-1 in SCCHN were characterised and analysed. RESULTS: The expressions of E-selectin and VCAM-1 were increased. The magnitude of expression was unrelated to the location or size of the primary tumour. With increasing de-differentiation, the expression of E-selectin increased, whereas the number of cells expressing VCAM-1 was highly variable. In contrast, E-selectin and VCAM-1 expressions decreased with progressive metastatic disease. CONCLUSIONS: These data demonstrate that the expression patterns of E-selectin and VCAM-1 may depend on differentiation and lymphogenic metastatic disease in SCCHN, and suggest that these molecules may have a dual role, depending on the stage of tumour development. These findings support the hypothesis that expression of E-selectin and VCAM-1 may be initiated by the release of tumour necrosis factor-alpha (TNF-alpha) at an early stage of tumour development. In contrast, the decrease in selectin expression, observed as the metastatic disease progresses, may serve as a protective mechanism to prevent an influx of effector cells.